2003
DOI: 10.1074/jbc.m306577200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 2 Is a Nuclear Protein and Inhibits DNA Synthesis

Abstract: Sphingosine kinase-1 (SPHK1) is a key enzyme catalyzing the formation of an important bioactive lipid messenger, sphingosine 1-phosphate, and is implicated in the regulation of cell proliferation and antiapoptotic processes. Biological features of another isozyme SPHK2, however, remain unclear. The present studies were undertaken to characterize SPHK2 by comparison with SPHK1. When SPHK2 was transiently expressed in various cell lines, it was localized in the nuclei as well as in the cytosol, whereas SPHK1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
349
7
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(382 citation statements)
references
References 21 publications
21
349
7
5
Order By: Relevance
“…We next examined whether SphK is involved in breast CSCs. Consistent with previous reports 32,33 , overexpressed SphK1 was localized in the cytosol, and SphK2 was mainly localized to the nucleus (Fig. 5a).…”
Section: S1p Increases Adam17 Activity Without Notch Ligandssupporting
confidence: 81%
“…We next examined whether SphK is involved in breast CSCs. Consistent with previous reports 32,33 , overexpressed SphK1 was localized in the cytosol, and SphK2 was mainly localized to the nucleus (Fig. 5a).…”
Section: S1p Increases Adam17 Activity Without Notch Ligandssupporting
confidence: 81%
“…We distinguished four fractions: (1) medium surrounding the cells, (2) cytosol, (3) nucleus and (4) the membranous compartments. Because the major FTY720 bio-activating enzyme SphK2 is located primarily in the nuclear and membranous compartments (Igarashi et al, 2003;Hait et al, 2009) we were interested to analyze how FTY720 and FTY720-P are distributed not only in wild type mice, but also in the splenocytes deficient for SphK2. Furthermore, our concern was to determine whether the distribution of FTY720 and FTY720-P is affected in the absence of the enzyme SphK1, phosphorylating S1P extranuclearly.…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast, overexpression of SphK2 does the opposite, suppressing cell growth and inducing apoptosis (26,27). Previously we have shown that mutation of leucine 219 in its putative BH3 domain, a highly conserved leucine present in all BH3 domains (28), reduced its ability to induce apoptosis (26) (Fig.…”
Section: Apoptosis Induced By Sphk2mentioning
confidence: 99%
“…These two isoenzymes have different kinetic properties and also differ in developmental and tissue expression (16), implying that they may have distinct physiological functions. Indeed, rather than promoting growth and survival, SphK2 suppressed growth and enhanced apoptosis that was preceded by cytochrome c release and activation of caspase-3 (26,27). Moreover, SphK2-induced apoptosis was independent of activation of S1P receptors (26).…”
mentioning
confidence: 99%